2015
DOI: 10.18520/cs/v109/i12/2198-2203
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Perceptions in a Technological Institution of Higher Education in India

Abstract: Institutions of higher education serve as models for excellence in education. They also have an added responsibility in providing guidance to the community for social upliftment and environmental sustainability. The present study conducted in the Indian Institute of Technology Roorkee examines the perception of the students on the importance of sustainability to the campus. One hundred sixty-five students participated in the survey. The survey focuses on three broad categories, namely environmental, educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Business school research improves organi-zations, systems, and social and environmental challenges, impacting the economy, law, and education. Climate, social structure, culture, traditional beliefs, and regulations affect Campus Sustainability approaches [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Business school research improves organi-zations, systems, and social and environmental challenges, impacting the economy, law, and education. Climate, social structure, culture, traditional beliefs, and regulations affect Campus Sustainability approaches [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…However, the idea of sustainability in the Indian higher education system is nascent and under-researched, which primarily addresses environmental issues [31]. Unfortunately, Indian universities generally focus only on the curriculum, the intake number, faculty development, facilities, necessary infrastructure but not enough thought has been given to the campus sustainability [32]. We can see only a few universities and institutes that practising only certain aspects of sustainability.…”
Section: Sustainability Issues In the Indian Higher Education Systemmentioning
confidence: 99%
“…The survey focuses on four broad categories, environmental, educational, research, and management factors also, the results showed that growing awareness on campus sustainability has resulted into specific practices in energy and transportation. Operational parameters of environmental factors are considered more important compared to the education and management parameters (Bantanur, Mukherjee, & Shankar, 2015) Additionally, a questionnaire survey at three Universities of the Comunidad Valenciana, Spain; with a total of 922 students answered the survey. A majority of respondents were not aware of the impact of their daily activities on the environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%